Demographic and clinical characteristics of 1092 consecutive police custody mental health referrals. Issue 3 (4th May 2017) - Forrester, Andrew; Samele, Chiara; Slade, Karen; Craig, Tom; Valmaggia, Lucia
Abstract: The 43 police forces in England and Wales have made over 13 million arrests in the last decade. Yet, despite this high volume criminal justice system activity, and evidence of substantial health morbidity across the criminal justice pathway, mental health services in police custody have only been patchily developed, and the literature in this area is limited. Referrals ( n  = 1092) to a pilot mental health service operating across two police stations in a London borough were examined over an 18-month period in 2012/2013. The referred group had high levels of mental health and substance misuse problems (including acute mental illness, intoxication and withdrawal), self-harm, suicide risk and vulnerability (including intellectual disability), with some important gender differences. Although this work has limitations, the findings are broadly consistent with the small existing literature and they confirm the need for services that are sufficiently resourced to meet the presenting needs.